2019
DOI: 10.1302/2058-5241.4.180036
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the femoral head: pathophysiology and current concepts of treatment

Abstract: Osteonecrosis of the femoral head is a disabling pathology affecting a young population (average age at treatment, 33 to 38 years) and is the most important cause of total hip arthroplasty in this population. It reflects the endpoint of various disease processes that result in a decrease of the femoral head blood flow. The physiopathology reflects an alteration of the vascularization of the fine blood vessels irrigating the anterior and superior part of the femoral head. This zone of necrosis is the source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
222
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(232 citation statements)
references
References 68 publications
0
222
0
10
Order By: Relevance
“…The prevalence of ON shows a significant variation (up to 10%) depending on age. Sickling of RBCs causes venous congestion, and thrombosis in the bone microvasculature resulting in ischemia that is enhanced by the increase of intraosseous pressure secondary to medullary hyperplasia [4,5]. Furthermore, elevated hemoglobin or hematocrit levels in combination with rheological problems lead to sickling and vaso-occlusion, especially in the femoral head sinusoids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of ON shows a significant variation (up to 10%) depending on age. Sickling of RBCs causes venous congestion, and thrombosis in the bone microvasculature resulting in ischemia that is enhanced by the increase of intraosseous pressure secondary to medullary hyperplasia [4,5]. Furthermore, elevated hemoglobin or hematocrit levels in combination with rheological problems lead to sickling and vaso-occlusion, especially in the femoral head sinusoids.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elevated hemoglobin or hematocrit levels in combination with rheological problems lead to sickling and vaso-occlusion, especially in the femoral head sinusoids. The most frequent identified ON sites are the hip (74.6%), shoulder, knee, and ankle [4,5]. The disease may involve the hips bilaterally, and it is common for ON to be asymptomatic, especially in early stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteonecrosis of the femoral head (ONFH) is a common orthopedic disease, which affects young and middle-aged patients originated from traumatic or non-traumatic issues. Without early intervention and appropriate treatment, up to 80% of ONFH cases eventually turn into femoral head collapse within 1 to 5 years [1][2][3]. Femoral head collapse is the most significant pathogenic complication of ONFH that requires total hip replacement eventually.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which onFH develops remains unclear (19). The majority of experts agree that a lack of blood supply to the femoral head and bone marrow causes death of osteocytes, as explained by the microvascular injury theory, osteoporosis theory, apoptosis theory, osteogenic enhancement and adipogenic weakening theory of bone marrow mesenchymal stem cells (20)(21)(22)(23)(24). it has previously been reported that numerous circrnas are associated with onFH, which suggested that they may have a critical role in the development and progression of onFH (25).…”
Section: Introductionmentioning
confidence: 99%